Liraglutide Is Protective against Brain Injury in Mice with Febrile Seizures by Inhibiting Inflammatory Factors. (29th April 2022) - Wang, Xing; Yang, Fei; Deng, Liling; Qiu, Di; Liu, Yao; Kang, Yang
Abstract : The febrile seizure (FS) is a common disease in emergency pediatrics, and about 30% of patients are children aged between 6 months and 5 years. Therefore, we aim to observe the protective impact of liraglutide (LIR) on brain injury in mice with FS and to explore its relevant mechanisms. Male SD mice were selected, and the FS model was established by heat bath method. The behavioral score was performed on mice with Racine grading, and nerve cells in apoptosis in the hippocampus were determined by TUNEL. The content of glutamate was determined by ELISA. mRNA levels and protein expression of GLP-1, GLP-1R, IL-1 β, IL-6, TNF- α, and cleaved-caspase 3 were examined in mice by q-PCR and WB. Protein expression of γ -aminobutyric acid was influenced by WB as well. LIR prolonged the seizure latency and seizure duration in mice with FS. The GLP-1 and GLP-1R in the mouse hippocampus with FS expressed highly and also inhibited the number of nerve cells in apoptosis, decreased glutamate content, and increased γ -aminobutyric acid expression in the mouse hippocampus with FS. In addition, The IL-1 β, IL-6, and TNF- α, in the mouse hippocampus with FS expressed to reduce with LIR. LIR is protective against brain injury in mice with FS and protects brain injury by inhibiting inflammatory factors in mice with FS. Our finding provides a reference for mitigating and delaying the development of FS as well as the prevention and treatment of brain injury caused by FS.